2018
DOI: 10.1038/s41598-018-30748-4
|View full text |Cite
|
Sign up to set email alerts
|

Humpback whale migrations to Antarctic summer foraging grounds through the southwest Pacific Ocean

Abstract: Humpback whale (Megaptera novaeangliae) populations typically undertake seasonal migrations, spending winters in low latitude breeding grounds and summers foraging in high latitude feeding grounds. Until recently, a broad scale understanding of whale movement has been derived from whaling records, Discovery marks, photo identification and genetic analyses. However, with advances in satellite tagging technology and concurrent development of analytical methodologies we can now detail finer scale humpback whale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 92 publications
0
81
0
Order By: Relevance
“…The STF lies within the Southern Tropical Convergence (STC) Three outhern right whales satellite tagged in South Africa also showed an association with the STC in the South Atlantic during the Austral summer months ( [28], and recent data from southern right whales tagged off Península Valdéz, Argentina, showed migratory movement of one female accompanied by a calf to latitudes associated with the STC [29]. Based on historical whaling data [30] and more recent telemetry studies, the STF south of Australia and New Zealand is suggested to be an important feeding for a number of other baleen whale species including pygmy blue whales [39] and humpback whales [50].…”
Section: Discussionmentioning
confidence: 99%
“…The STF lies within the Southern Tropical Convergence (STC) Three outhern right whales satellite tagged in South Africa also showed an association with the STC in the South Atlantic during the Austral summer months ( [28], and recent data from southern right whales tagged off Península Valdéz, Argentina, showed migratory movement of one female accompanied by a calf to latitudes associated with the STC [29]. Based on historical whaling data [30] and more recent telemetry studies, the STF south of Australia and New Zealand is suggested to be an important feeding for a number of other baleen whale species including pygmy blue whales [39] and humpback whales [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, the extensive longitudinal movements (>1500 km) observed from east to west of the Coral Sea further question the scale at which the humpback whale may move during the breeding season. Longitudinal movements were characterized by transit-like parameters, typically observed during migration: low residence time, high swimming speeds and oriented travelling 10,11,[36][37][38] . Two males moved between the well-known breeding grounds of southeastern New Caledonia, and the presumed breeding grounds of Capel and Kelso, located at a distance of about 850 km.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a decrease in the size of phytoplankton can cause a significant change in the local trophic web and in biogeochemical cycles (Rozema et al, 2017;Aracena et al, 2018;Da Cunha et al, 2018). It is possible that changes in the phytoplankton community and the seasonality of krill lead to population decreases in penguins (Sander et al, 2007), changes in the benthic community (Montes-Hugo et al, 2009) and variation in the period and frequency of migratory movements of humpback whales (Johnston et al, 2012;Andrews-Goff et al, 2018).…”
Section: The Relationship Between Microphytoplankton Community Structmentioning
confidence: 99%